Acute Acromioclavicular Joint Dislocation Stabilized by Mini-Open Double Endo-Button and Fiber Wire System (Journal of Nobel Medical College, 2025)
Background: There are different surgical treatment options for acromioclavicular joint dislocation which can be done by open, mini-open or arthroscopically. We aimed to evaluate mini-open double endo-button and fiber wire for stabilization of Rockwood type III, IV and V acromioclavicular joint dislocation.Materials and Methods: This is a prospective clinical cohort study performed between April 2021 to March 2023. All  cases were treated by mini-open double endo-button and fiber wire. Age, sex, injury mechanism, side of injury, time before surgery, duration of hospital stay, constant score, disability of Arm, Shoulder and Hand score (DASH), visual analogue scale (VAS), coracoclavicular distance and complications were recorded during follow up.Results: Out of 25 cases, 20(80%) were male and 5(20%) were female. The mean age of patients was 33.64±9.83. The mean DASH and constant score were 1.58±1.03  and 93.84±3.15 respectively. There was significant decrease in VAS score. There was no significant difference in coracoclavicular distance between injured and contralateral side. Three cases had residual subluxation.Conclusion: The mini-open double endo-button and fiber wire technique of fixation is excellent method for dislocated acromoiclavicular joint without any soft tissue dissection around coracoclavicular ligaments.